Karbon Tersimpan pada Pohon Trembesi (Albizia saman) di Kawasan BSD (Bumi Serpong Damai) 2 Tangerang Selatan - Kristiyanto Kristiyanto (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The BSD 2 urban area (City Park) is part of the green area development, and this can support the stability of the urban ecosystem in creating balanced ecological conditions within it, and of course there are many types of trees, such as Livistona saribus, Roystonea regia, Carbera manghas, and Elais guineensis in the BSD 2 area, but only one type of tree was studied, namely the Albizia saman tree, where ± 122 trees were found. This research aims to estimate and analyze the stored carbon (carbon stock) in Albizia saman trees, while the sampling method is random sampling and line transects, as well as the carbon stock measurement method by measuring biomass in the stands. The results of this research show that the average at a diameter of 0<10 m is 60.09 tons C/ha, then at a diameter >70<80 m it is 43048.86 tons C/ha, while the diameter of the tree is the largest in storing carbon found in diameters >40<50 m is 58326.43 tonnes C/ha. The conclusion of this research shows that the Albizia saman tree has a big role and contribution in reducing air pollution (CO2), so this becomes a reference or guideline for all parties, both government and society, to be able to cultivate and preserve this tree species in a good and sustainable manner. to support the development of the "Eco City" paradigm.